2008
DOI: 10.1007/s10147-007-0690-x
|View full text |Cite
|
Sign up to set email alerts
|

Complete response of a pancreatic adenosquamous carcinoma to chemoradiotherapy

Abstract: A 51-year-old woman with an unresectable pancreatic tumor that was histologically diagnosed as an adenosquamous carcinoma underwent chemoradiotherapy with 5-fluourouracil (FU) and low-dose cisplatin (low-dose FP). Because we recognized a partial response to the chemoradiotherapy, we subsequently administered combined chemotherapy with S-1 and cisplatin. After one course of this combined chemotherapy, the tumor was further reduced in size and became difficult to discern on abdominal computed tomography (CT). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…There have been several case reports and a few case series reporting on PASC [6,11,15-33]. To our knowledge, this study is the largest single institution study (n = 38) to specifically examine the impact of adjuvant chemoradiation on outcome of patients with resected PASC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several case reports and a few case series reporting on PASC [6,11,15-33]. To our knowledge, this study is the largest single institution study (n = 38) to specifically examine the impact of adjuvant chemoradiation on outcome of patients with resected PASC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the optimal management of these patients in the postoperative adjuvant period remains poorly defined. Only a few anecdotal studies regarding the efficacy of adjuvant chemotherapy and radiation treatment of PASC have been published [5,6,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…PASC regimens are proposed in accordance with those of pancreatic adenocarcinoma, including a monotherapy of S-1, or a combination therapy of S-1 plus gemcitabine, or an S-1 plus platinum-and/or a paclitaxel-based chemotherapy [12][13][14][15]. Squamous carcinoma is considered to be susceptible to radiation therapy, and postoperative radiation therapy has been found to yield some favorable results [16].…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary treatments including aggressive surgery, intraoperative radiation therapy, and locoregional chemotherapy have also been reported to improve the survival of patients with adenosquamous carcinoma of the pancreas and to inhibit liver metastasis and local recurrence [12]. Shibagaki K et al presented a case of successful use of chemoradiotherapy with low-dose cispastin and additional combined chemotherapy with S-1 and cisplatin for unresectable pancreatic adenosquamous carcinoma [13]. Tanaka N et al suggested that combined chemotherapy with cytokines (IFN-a plus TNF-a) and 5-FU may be a therapeutic modality for advanced pancreatic cancer [14].…”
Section: Discussionmentioning
confidence: 99%